2003
DOI: 10.1002/prot.10523
|View full text |Cite
|
Sign up to set email alerts
|

ProVal: A protein‐scoring function for the selection of native and near‐native folds

Abstract: A low-resolution scoring function for the selection of native and near-native structures from a set of predicted structures for a given protein sequence has been developed. The scoring function, ProVal (Protein Validate), used several variables that describe an aspect of protein structure for which the proximity to the native structure can be assessed quantitatively. Among the parameters included are a packing estimate, surface areas, and the contact order. A partial least squares for latent variables (PLS) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Overall, our results appear to perform better than other scoring functions published in the literature that were tested on the same or similar decoy sets. The published scoring functions can be divided into physically derived energy functions (Dominy and Brooks, 2002;Felts et al, 2002;Gatchell et al, 2000;Hsieh and Luo, 2004;Lazaridis and Karplus, 1999;Narang et al, 2006;Petrey and Honig, 2000;Zhu et al, 2003), similar in spirit to our energy function presented here, and those that are generated as a statistical scoring function based on the frequency of observations of atom or residue contacts in the PDB database, and sometimes combined with physical forces (Berglund et al, 2004;Dehouck et al, 2006;Fain et al, 2001;McConkey et al, 2003;Mukherjee et al, 2005;Shen and Sali, 2006;Wang et al, 2004). While it might seem an advantage to use knowledge-based scoring functions since they are believed to be more reliable in protein structure prediction, we found that our energy function does significantly better in both the native ranking and the native Z score, especially for the most challenging Rosetta sets, which generate $1000-2000 decoys with native-like features.…”
Section: Structurementioning
confidence: 99%
“…Overall, our results appear to perform better than other scoring functions published in the literature that were tested on the same or similar decoy sets. The published scoring functions can be divided into physically derived energy functions (Dominy and Brooks, 2002;Felts et al, 2002;Gatchell et al, 2000;Hsieh and Luo, 2004;Lazaridis and Karplus, 1999;Narang et al, 2006;Petrey and Honig, 2000;Zhu et al, 2003), similar in spirit to our energy function presented here, and those that are generated as a statistical scoring function based on the frequency of observations of atom or residue contacts in the PDB database, and sometimes combined with physical forces (Berglund et al, 2004;Dehouck et al, 2006;Fain et al, 2001;McConkey et al, 2003;Mukherjee et al, 2005;Shen and Sali, 2006;Wang et al, 2004). While it might seem an advantage to use knowledge-based scoring functions since they are believed to be more reliable in protein structure prediction, we found that our energy function does significantly better in both the native ranking and the native Z score, especially for the most challenging Rosetta sets, which generate $1000-2000 decoys with native-like features.…”
Section: Structurementioning
confidence: 99%
“…We have recently published a low-resolution scoring function ProVal [56] developed with PLS that uses a multipole representation of side chains centered on the carbon alphas and betas that can distinguish the correct structure in the midst of plausible decoy folds in a large percentage of the 28 test cases studied (Figure 1.7). For 18 of the protein sets (∼64%), the crystal structure scored best.…”
Section: Protein Structure Predictionmentioning
confidence: 99%
“…The quality assessment of models has been the focus of numerous studies and various algorithms exist with scoring functions based on statistical potentials [10], local side-chain and backbone interactions [11], residue environments [12], packing estimates [13], solvation energy [14], hydrogen bonding, and geometric properties [15]. In addition, the proper stereochemistry of models can be assessed by commonly used programs such as Procheck or WhatIf [16,17].…”
Section: Introductionmentioning
confidence: 99%